PROBLEMS OF COMBATING CORRUPTION: INTERNATIONAL EXPERIENCE AND PRACTICE OF EU MEMBERS - Valijonov, Daler (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The author of the article examines the current issues of combating corruption in the context of global and regional integration, in particular, the experience of institutional mechanisms to combat corruption on the example of the countries of the European continent. In particular, the highly successful experience of Sweden, Denmark, Finland and Norway is analyzed. The article indicates the international legal framework of the institutional framework for combating corruption in the global arena. Along with this, the author puts forward proposals on mechanisms that contribute to reducing the level of corruption in the Republic of Uzbekistan.